The Glamour System - Gundle, S. author. aut Link
VII, 211 p.
Keywords: In the twentieth century, glamour has often been associated with the cinema and its stars, though fashion, 'high society', popular music, shopping, glossy magazines and advertising have all sought to harness its allure. The authors explore the origins and uses of the aura of glamour and trace its history and power as a language of visual seduction.